Do silêncio ao grito: o modo de figuração das vozes em Levantado do chão, de José Saramago - Steffler, Luana Catita (2019)
"From Silence to scream: The figuration mode of the voices in Levantado do Chão, by José Saramago" has as object of study the 1980 novel that narrates the saga of Alentejo peasants in Portugal during three quarters of a century, more than forty years under the Salazarista military dictatorship. In the work, the author laureate with the Nobel Prize for Literature in 1998, with compassion and irony makes understandable a forgotten reality in narrating the life of a family of farmers in southern Portugal. As the protagonists present the novel constructs a panorama of the context, it forms a comprehensive vision of the way of life not only of them, but of those who explore them. With a vigorous writing in denouncing the misery, exploitation and violence against the people, the author relates the different perspectives that tell the story – of the landlord, the clergy and the workers -, corroborating them in order to prevail an empathic reading with the point of view of those who have been wronged. The representation of social discourses in the novel is theoretically supported by Mikhail Bakhtin's linguistic-literary approach. The organization of these perspectives in a structure that corroborates that opposing points of view culminate in a defensive reading of the ideology of the protagonists, due to the conduction and constant intervention of the narrator, is approached in this work based on the structuring perspective theorizing of the contemporary narratology scholar Ansgar Nunning. In the development of the narrative, it is also perceived throughout the three generations of the Mau-Tempo family, the change in the discourse of Alentejo peasants, whose level of political consciousness is non-existent, is awakened by learning about the need for a struggle for rights that they are denied them and progresses until they take an attitude towards the bosses, to achieve a less exhaustive working day, a decent salary and possession of the cultivated lands. In this dissertation, therefore, a reflection on the different social voices narrated in Levantado do Chão, and how they are configured in an organization of parallel and interrelated perspectives, according to the direction of the saramaguian narrator, whose narration defends the ideological perspective of the portuguese workers and their discourse that modifies progressively in the novel.